Simple measurement of aneurysm residual after treatment: the SMART scale for evaluation of intracranial aneurysms treated with flow diverters. - Grunwald, I; Kamran, M; Corkill, R; Kühn, A; Choi, I; Turnbull, S; Dobson, D; Fassbender, K; Watson, D; Gounis, M (2012)
BACKGROUND: Primary endovascular reconstruction with flow diversion represents a fundamental paradigm shift in the technique of endovascular aneurysm treatment. Unlike coil embolization, often there remains residual post-procedural filling within the aneurysm with flow diverters, the curative reconstruction presumably occurring over a period of weeks. Thus, conventional grading scales for post-procedural aneurysm occlusion and recanalization are inadequate. The aim of this paper is to propose a new angiographic grading scale that addresses this fundamentally new treatment option. METHOD: A five-point grading scale describes the location of residual flow within the aneurysm in the venous phase [grade 1: patent aneurysm with diffuse inflow; grade 2: residual filling of the aneurysm dome (saccular) or wall (fusiform); grade 3: only residual neck (saccular) or only intra-aneurysmal filling with former boundaries covered (fusiform); grade 4: complete occlusion]. FINDINGS: Grade 0 represents any aneurysm, regardless of occlusion rate with early phase, coherent inflow jet. Intra-aneurysmal flow stagnation is categorized into: (a) none, (b) capillary phase, and (c) venous phase. Prevailing parent vessel hemodynamics with in-stent stenosis (ISS) are divided into none (ISS0), mild (ISS1), moderate (ISS2), severe (ISS3), and total (ISS4) occlusion. The proposed grading scales allow assessment of the hemodynamic consequences of stent placement on endosaccular in-flow, stasis, and location of stasis as well as parent vessel hemodynamics. CONCLUSIONS: Further studies need to show the applicability and possible predictive value of this new grading scale on the efficacy of the stent in promoting intra-aneurysmal flow stagnation, thus creating the potential to harmonize the results of future papers. This may help to optimize treatment and future device design.